Suspicion, violence, and social distance: everyday discretion in the South African Police - OFaolain, Sian Miranda Singh (My University, 2010)
Abstract This dissertation contributes to the policing field by using empirical observations about police work to demonstrate the importance of street-level police officers' perceptions of their own work and their relation to the public. By taking discretion as the moment of interaction between a police officer and a civilian, the dissertation adopts a theoretical framework arguing that everyday types of discretion must be examined to offer insight into broader questions around police accountability and practices. Rather than focusing on discretion as granted by the law, or seeking to limit officers' ability to use their discretion, the research argues that the moments of decision-making reveal trends and patterns in more cultural terms. Adding to the empirical, observational data on the South African Police Service, this dissertation approaches the police by looking at the role of discretion in police decision-making. In this way, the work seeks to move away from studies that discuss police organizational culture, in an effort to readjust the focus to the police side in interactions with the civilians they are meant to police and protect. The three empirical chapters focus on spatially-constructed suspicion and profiling, the relationships that officers have to the threat of violence in their daily work, and the role of food sharing and food exchange in revealing social distance among the police force. By focusing on the meanings that police produce during their work, and more importantly, the stereotypes, assumptions, and fears that compel them to act in certain ways, the work offers a new lens through which to view the reality of police work on the ground.